Increasing Inmate’s Resilience with Support Group Therapy - Adisty Rose Artistin; Eny Purwandari; Rr Pujiastuti Sri Endang; Shoim Muhammad Sulaiman; Depy Eka Rachmawati (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
The prevalence of mental disorders in prison inmates (WBP) has increased due to high stressors in the correctional environment. Inmate’s stress comes from difficulties in adjusting to prison life with the obligation to follow applicable rules, being separated from family, losing goods and services, losing freedom and losing patterns of sexuality One way to deal with stress is to provide social support which can also increase resilience. The research aims to identify the increased resilience of prisoners after being given support group therapy. The research was conducted using a quasi-experimental method with a one group pretest-posttest design model. The population of this study were inmates who are in Class II Ambarawa Penitentary. The sample in this study was determined by non-random sampling with inclusion criterias are inmates who behaved well while in the correctional environment, aged over 17 years and had a low to moderate resilience score. The sample in this study consisted of 10 inmates who have low-moderate levels of resilience based on the Connor-Davidson Resilience Scale 25 (CD-RISC 25). Data were collected in two months between September-Novermber 2022. Data were analyzed using different test of independent sample t-test. The results showed that there was an increase in the resilience of the respondents after being given support group therapy. Inmates can provide social support in correctional facilities through support group therapy in order to increase the resilience level of other prisoners.  Keyword: Inmate , Resilience, Support group therapy